Body and carcass weight losses in goats during the advanced periods of the West African Sahelian dry seasons - Alaku, O.; Moruppa, S.M. (1983)
Data were collected from a total of 268 (137 Borno white and 131 Red Sokoto) goats slaughtered in the Maiduguri abbatoir from December 1981 to May 1982 to investigate the actual body and carcass weight losses of the two breeds during the study period. Mean ± S.E. for both body and hot carcass weight were calculated for each breed for each month. And all data were subjected to analysis of variance. Month of slaughter significantly (P